Pengaruh Ngulat Tipat Taluh terhadap Keterampilan Motorik Halus Anak Usia 6-7 Tahun - Bajirani, Made Padma Dewi; Susilawati, Luh Kadek Pande Ary (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2014)
Fine motor skills are very important skills that needed in child development and it require training and skills to be developed. However, there are only few of fine motor skills development which based on culture and uses traditional activities to be the tool to improve the child’s fine motor skills. In Balinese culture, one of activities which can be used to develop fine motor skill is ngulat tipat taluh. Based on this problem, the aim of this study was to determine the effect of ngulat tipat taluh to fine motor skills in children aged 6-7 years. This study used an experimental method with one-group pre-test post-test design with 49 people as subject. Data in this study was collected by measuring fine motor skills variable in pre-test and post-test. The measurement is using mazes that consist of 8 items, and after the validity and reliability test each items was valid with rix in range 0.298 to 0.712 and alpha cronbach reliability coefficient (?) is 0.812. Based on the results of the statistical paired T-test, the value of significance (2-tailed) 0.00 ? 0.025 (? = 0.025) and the t value in this study was 6.603 greater than t table (1.677). Based on statistical analysis, it can be concluded that the alternative hypothesis (Ha) can be accepted and there was significant influence ngulat tipat taluh to fine motor skills in 6-7 years old children. Keywords: Ngulat tipat taluh, fine motor skills, children aged 6-7 years.